Kalanchoe steyniae (Crassulaceae subfam. Kalanchooideae; K. [subg. Kalanchoe sect. Raveta] ser. Rotundifoliae), a new, small-growing, shrubby species from eastern southern Africa - Smith, Gideon F.; Crouch, Neil R. (Phytotaxa, 2024)
A new species of Kalanchoe (K. [subg. Kalanchoe sect. Raveta] ser. Rotundifoliae; Crassulaceae subfam. Kalanchooideae), K. steyniae, is described from the northeastern parts of South Africa’s KwaZulu-Natal province and neighbouring Eswatini in eastern southern Africa. Kalanchoe steyniae differs from K. rotundifolia in especially reproductive characters, with, inter alia, its flowers being densely arranged (not diffusely so) in ± flat-topped, corymbose cymes; its corolla lobes showing weak (not distinct) diurnal movement; its sepals being longer; and its corolla tubes and corolla lobes being bright crimson red (not dull red to orange). Both species are illustrated.